Laparoscopic intersphincteric resection vs. transanal total mesorectal excision in overweight patients with low rectal cancer - Li, Zhengbiao; Wang, Qi; Feng, Qingbo; Wang, Xingqin; Xu, Fujian; Xie, Ming (Frontiers in Surgery, 2022)
Objective Anus-preserving surgery in overweight patients with low rectal cancer has been a challenge due to the narrow operating space.Intersphincteric resection(ISR) was once a standard therapeutic option for low rectal cancer. The effectiveness of transanal total mesorectal excision (taTME) in treating this group of patients remains uncertain as a new surgical strategy. The aim of this study was to evaluate the short-term effects of taTME with ISR in overweight patients with low rectal cancer. Methods A total of 53 patients with low rectal cancer were treated with taTME in 31 cases and ISR in 22 cases. The surgery-related data, pathological manifestations of surgical specimens, postoperative recovery ,and postoperative complications were compared. Results Patients in both groups completed the surgery successfully. There were no significant differences in operative time, blood loss, anastomotic distance from the anal verge and ileostomy between the two groups (P > 0.05). TaTME group performed or virtually finished resection of the rectal mesentery, and no positive cases of Circumferential Resection Margin (CRM) or Distal Resection Margin (DRM) were detected in either group. The number of lymph nodes found in surgical specimens did not change significantly between the two groups (P=0.391). In the subgroup analysis, however, more lymph nodes were detected in female patients undergoing taTME than in male patients (P=0.028). The ISR group took less time to remove the drainage tubes (P=0.013) and the same results were obtained in both groups of male patients in the subgroup analysis (P=0.011). There were no statistically significant differences in time to start liquid diet, time to remove catheters, time to start flatus, time to begin ambulation, postoperative hospital stay, and readmission within 30 days after surgery between the two groups(P > 0.05). However, female patients in the taTME group were initiated ambulation earlier than males in the subgroup analysis (P=0.034). The difference was insignificant in the occurrence of postoperative complications between the two groups (P > 0.05). Conclusion taTME is safe and feasible for the treatment of overweight patients with low rectal cancer but has the potential to prolong the removal of drainage tubes.